2015
DOI: 10.7554/elife.05457
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of prefrontal and parietal cortex inactivations on an accumulation of evidence task in the rat

Abstract: Numerous brain regions have been shown to have neural correlates of gradually accumulating evidence for decision-making, but the causal roles of these regions in decisions driven by accumulation of evidence have yet to be determined. Here, in rats performing an auditory evidence accumulation task, we inactivated the frontal orienting fields (FOF) and posterior parietal cortex (PPC), two rat cortical regions that have neural correlates of accumulating evidence and that have been proposed as central to decision-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
292
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(346 citation statements)
references
References 88 publications
34
292
8
Order By: Relevance
“…In this control task, monkeys chose freely between two saccade targets in the absence of a motion stimulus. Inactivation in LIP shifted choices away from the target in the contralesional hemifield, consistent with previous inactivation studies in monkeys, rodents, and humans (Balan & Gottlieb 2009, Erlich et al 2015, Kerkhoff 2001, Kubanek et al 2015, Wardak et al 2002, Wilke et al 2012, Zirnsak et al 2015), and indicating that neural activity in LIP—although necessary for guiding free choices—is not necessary for the type of perceptual decision traditionally used to elicit decision-correlated activity in LIP.…”
Section: Causal Interrogations Of Lip and Distributed Processing Forsupporting
confidence: 87%
“…In this control task, monkeys chose freely between two saccade targets in the absence of a motion stimulus. Inactivation in LIP shifted choices away from the target in the contralesional hemifield, consistent with previous inactivation studies in monkeys, rodents, and humans (Balan & Gottlieb 2009, Erlich et al 2015, Kerkhoff 2001, Kubanek et al 2015, Wardak et al 2002, Wilke et al 2012, Zirnsak et al 2015), and indicating that neural activity in LIP—although necessary for guiding free choices—is not necessary for the type of perceptual decision traditionally used to elicit decision-correlated activity in LIP.…”
Section: Causal Interrogations Of Lip and Distributed Processing Forsupporting
confidence: 87%
“…This is of possible broader interest, for example, in linking to rodent work (Erlich et al, 2015, Scott et al, 2015, Morcos and Harvey 2016, Pinto et al, 2017, Odoemene et al, 2017, Licata et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In other instances, however, “late weighting” has been observed, where choices were primarily influenced by sensory evidence presented in late stimulus epochs (Tsetsos et al, 2012; Cheadle et al, 2014; Bronfman et al, 2016; Carland et al, 2016). In rodents, a mixture of either early or flat weighting profiles has been reported (Erlich et al, 2015; Scott et al, 2015; Pinto et al, 2017; Licata et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Another body of experiments, performed both in primates and in rodents, indicated a role of PPC in decision making, especially for decisions based on vision (Andersen and Cui, 2009;Erlich et al, 2015;Goard et al, 2016;Gold and Shadlen, 2007;Katz et al, 2016;Latimer et al, 2015;Licata et al, 2017;Platt and Glimcher, 1999;Raposo et al, 2014;Sugrue et al, 2004). Studies in rodents found decision signals to be widespread in PPC populations, where they are mixed with other signals (Goard et al, 2016;Raposo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%